The dominant temperature-sensitive lethal DTS7 of Drosophila melanogaster encodes an altered 20S proteasome beta-type subunit. - Smyth, K.A.; Belote, J.M. (Genetics, 1999)
Proteasomes are multicatalytic complexes that function as the major proteolytic machinery in regulated protein degradation. The eukaryotic 20S proteasome proteolytic core structure comprises 14 different subunits: 7 alpha-type and 7 beta-type. DTS7 is a dominant temperature-sensitive (DTS) lethal mutation at 29 degrees that also acts as a recessive lethal at ambient temperatures. DTS7 maps to cytological position 71AB. Molecular characterization of DTS7 reveals that this is caused by a missense mutation in a beta-type subunit gene, beta2. A previously characterized DTS mutant, l(3)73Ai1, results from a missense mutation in another beta-type subunit gene, beta6. These two mutants share a very similar phenotype, show a strong allele-specific genetic interaction, and are rescued by the same extragenic suppressor, Su(DTS)-1. We propose that these mutants might act as "poison subunits," disrupting proteasome function in a dosage-dependent manner, and suggest how they may interact on the basis of the structure of the yeast 20S proteasome.